Cultivating the Field in the Global Hinterland: Community Building for Mass Housing in the Amazon Region. (July 2016) - Hehl, Rainer
Abstract : The large‐scale residential settlements that have sprung up over the last decade to house migrants flocking to join Brazil's burgeoning rural industries are in urgent need of retrofitting with infrastructure and community facilities if they are to become sustainable. To this end, international urban design practice the BAÚ Collaborative has initiated the 'Eden' project – a participatory design process that involves state authorities, local NGOs, residents and social workers.Rainer Hehl, a cofounder of BAÚ, outlines the problem, the project, and its test‐site: the mining town of Parauapebas.